DETECTION AND QUANTIFICATION OF ENVIRONMENTAL POLLUTION CAUSED BY STATIN AND ANTIFUNGAL DRUGS - Nadeem Kizilbash (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Lipophilic drugs, such as Simvastatin, Atorvastatin, Ketoconazole and Clotrimazole are present in the waste water in complex matrices. As a result, it is very difficult to detect them by conventional chromatographic methods since high flow rates are used in LC along with volatile buffers. The thermally labile nature of these compounds makes them difficult to detect. LC-UV and LC-MS are promising methods for detection of these drugs. In this review, the efficacy of these two techniques is discussed for the detection of these four lipophilic drugs